Under the Cartagena Protocol on Biosafety – Where is the Roadmap for Risk Assessment Taking Us? - Gaugitsch, Helmut (Frontiers in Bioengineering and Biotechnology, 2016)
The paper summarizes the history of the development of the guidance on risk assessment, including the roadmap under the Cartagena Protocol on Biosafety since 2008 until now. The aim and the contents of the roadmap for risk assessment of living modified organisms (LMOs) are described, in particular the five steps in the risk assessment process. After several rounds of discussions at the expert and political level, the guidance including the roadmap is currently revised taking into account the results of an in-depth practical testing process by the Parties, Non-Parties, and relevant organizations. The aim is to provide an improved version of the guidance for endorsement and broad support by the next meeting of the Parties to the Cartagena Protocol in December 2016.